Penggunaan Media Whatsapp pada Pembelajaran serta Pengaruhnya terhadap Motivasi dan Gaya Belajar Siswa Selama Pandemi Covid-19 - Hary Murcahyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of using WhatsApp media on students' motivation and learning styles during the Covid-19 pandemic. The type of research used is descriptive quantitative research. The subjects of this study were 115 students with a sampling technique that was proportionate stratified random sampling while the data collection technique used was a questionnaire. Data analysis techniques using hypothesis testing. The results of this study are that learning using WhatsApp has a positive effect on motivation, especially on the indicators of diligence, punctual, tenacity, courage to ask, curiosity, happy and active. In addition, learning using WhatsApp also has a positive effect on learning styles, especially in the very high visual learning style indicator, but medium auditory learning style, and low kinesthetic learning style because it doesn't require much movement. The conclusion of this study is that the use of WhatsApp media in learning has a positive effect on motivation and learning styles during Covid-19. Keywords: Learning styles, Learning Motivation, WhatsApp